2013
DOI: 10.1017/s0144686x13000627
|View full text |Cite
|
Sign up to set email alerts
|

How ‘age-friendly’ are rural communities and what community characteristics are related to age-friendliness? The case of rural Manitoba, Canada

Abstract: Since the World Health Organization introduced the concept of ‘age-friendly’ communities in 2006, there has been rapidly growing interest in making communities more age-friendly on the part of policy makers world-wide. There is a paucity of research to date, however, that has examined age-friendliness in diverse communities, particularly in rural communities. The main objective of the study reported in this paper was to examine whether age-friendliness varies across community characteristics, such as a populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 37 publications
0
39
0
4
Order By: Relevance
“…For example, 33% of Canadian older adults live in rural areas (Dandy & Bollman, 2008). In recent years several provinces in Canada have launched age-friendly initiatives in rural areas after discussions with rural communities identified age-friendly features that were similar to those in cities (Menec et al, 2013). Transportation issues were found to be magnified in rural areas, as well as a lack of access to social and healthcare services (Canada, 2006).…”
Section: Critiquementioning
confidence: 99%
“…For example, 33% of Canadian older adults live in rural areas (Dandy & Bollman, 2008). In recent years several provinces in Canada have launched age-friendly initiatives in rural areas after discussions with rural communities identified age-friendly features that were similar to those in cities (Menec et al, 2013). Transportation issues were found to be magnified in rural areas, as well as a lack of access to social and healthcare services (Canada, 2006).…”
Section: Critiquementioning
confidence: 99%
“…The US measure of county affluence was also significantly associated with increased doctor supply. While access to other services such as shopping, employment, cultural and other recreational opportunities was not directly measured, it is known that these services are all strongly related to population size 51 . Additionally, while poorer access to schools was not significant within the Australian models, this measure is strongly correlated with population size and shown to be a major reason for dissatisfaction of doctors living in smaller rural areas or not taking up rural practice in the first instance 6,9,26 .…”
mentioning
confidence: 99%
“…This group of people did not appreciate seeing a different doctor each time they required medical services. Studies undertaken in rural Canada found that the provision of appropriate and consistent primary health‐care services to older communities was influenced by the ability to recruit and retain health professionals including physicians . Difficulties with recruitment and retention lead to the utilisation and reliance on “locum” or casual health professionals, a common feature in the provision of primary health care in rural areas …”
Section: Discussionmentioning
confidence: 99%
“…Studies undertaken in rural Canada found that the provision of appropriate and consistent primary health-care services to older communities was influenced by the ability to recruit and retain health professionals including physicians. 24 Difficulties with recruitment and retention lead to the utilisation and reliance on "locum" or casual health professionals, a common feature in the provision of primary health care in rural areas. 25 As evident in the narratives, nurses were reported as being central figures in the provision of health services, including being first point of contact when a doctor was not available, as well as providing a diverse range of health services both inside clinics and in community settings (eg house calls by district nurses).…”
Section: Discussionmentioning
confidence: 99%